Endoplasmic Reticulum Stress and Its Role in Homeostasis and Immunity of Central and Peripheral Neurons - Perner, Caroline; Krüger, Elke (Frontiers in Immunology, 2022)
Neuronal cells are specialists for rapid transfer and translation of information. Their electrical properties relay on a precise regulation of ion levels while their communication via neurotransmitters and neuropeptides depends on a high protein and lipid turnover. The endoplasmic Reticulum (ER) is fundamental to provide these necessary requirements for optimal neuronal function. Accumulation of misfolded proteins in the ER lumen, reactive oxygen species and exogenous stimulants like infections, chemical irritants and mechanical harm can induce ER stress, often followed by an ER stress response to reinstate cellular homeostasis. Imbedded between glial-, endothelial-, stromal-, and immune cells neurons are constantly in communication and influenced by their local environment. In this review, we discuss concepts of tissue homeostasis and innate immunity in the central and peripheral nervous system with a focus on its influence on ER stress, the unfolded protein response, and implications for health and disease.